2021
DOI: 10.3389/fmicb.2021.730045
|View full text |Cite
|
Sign up to set email alerts
|

The 5′ and 3′ Untranslated Regions of the Japanese Encephalitis Virus (JEV): Molecular Genetics and Higher Order Structures

Abstract: The untranslated region (UTRs) of viral genome are important for viral replication and immune modulation. Japanese encephalitis virus (JEV) is the most significant cause of epidemic encephalitis worldwide. However, little is known regarding the characterization of the JEV UTRs. Here, systematic analyses of the UTRs of JEVs isolated from a variety of hosts worldwide spanning about 80 years were made. All the important cis-acting elements and structures were compared with other mosquito-borne Flaviviruses [West … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Our previous study [ 5 ] identified that a 300 nt-length region located at the beginning of the JEV 3’UTR, termed variable region (VR), exhibited significant genotypic specificity. In this study, the VR region of the 115 JEV sequences was also analyzed to verify whether the genomic sequences of the emerging JEV GIV conform to the phylogenetic characteristics of the JEV population.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study [ 5 ] identified that a 300 nt-length region located at the beginning of the JEV 3’UTR, termed variable region (VR), exhibited significant genotypic specificity. In this study, the VR region of the 115 JEV sequences was also analyzed to verify whether the genomic sequences of the emerging JEV GIV conform to the phylogenetic characteristics of the JEV population.…”
Section: Methodsmentioning
confidence: 99%
“…The genome length of JEV is about 10,965 nt and contains a single open reading frame (ORF) encoding a polyprotein that is processed into three structural (C, M, and E) and seven nonstructural (NS1, NS2A, NS2B, NS3, NS4A, NS4B, and NS5) proteins [ 3 , 4 ]. The 5′ and 3’ untranslated regions (UTR) are located on both sides of the ORF and contain abundant cis-acting elements that are crucial for virus replication, immunity, and pathogenicity [ 5 ]. Previous studies have indicated three domains in E protein, and the E protein domain III, which has the main cites for neutralizing antibodies, is considered to play a key role in activating receptor and membrane fusion [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…JEV has a single-stranded RNA genome that contains only an open reading frame (ORF) flanked by the 5’ and 3’ untranslated regions [ 4 ]. The ORF encodes three structural proteins [capsid (C), pre-membrane (prM), and envelope (E) proteins] and seven non-structural (NS) proteins (NS1, NS2a, NS2b, NS3, NS4a, NS4b, and NS5) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, to our knowledge, two studies have utilized unbiased techniques to examine the CSF proteome in human patients with confirmed JEV infection; while they demonstrate the feasibility of the methods, the patients were not confirmed by seroneutralization and included relatively small numbers of patients (10 and 26 JE patients). , There have been a handful of studies utilizing ELISA methods to target specific proteins; however, these rarely used power calculations in their experimental design, nor did they include adequate controls. Analysis of the transcriptome and proteome in animal models and cell culture ,, have been performed; however, the comparability to human CSF and comparison with other neurological infections is limited. Furthermore, mRNA expression does not directly correlate with that of the corresponding protein …”
Section: Discussionmentioning
confidence: 99%